The Relevance of George Orwell: Reflections on the Teaching and Learning of History in a Knowledge Based Curriculum. Issue 2 (1st July 2016) - Percival, James
Abstract : George Orwell's reflections on his own preparatory school education, and his subsequent work as an unqualified private school teacher, highlight many of the weaknesses associated with a factual and rote based teaching and learning of history. These insights are timely given the return to a knowledge-based curriculum in the recent National Curriculum reforms. The longstanding debate between progressive and traditionalist approaches to history is outlined and a case made that ultimately historical understanding requires both knowledge and skills. Orwell also identified the importance of visual imagery as a starting point for historical reasoning, something that has rarely received recognition from history educators.